Efficient Charging of Lithium–Sulfur Batteries by Triboelectric Nanogenerator Based on Pulse Current. Issue 2 (25th October 2018) - Yin, Yingying; Zhang, Xiuling; Du, Xinyu; Zhou, Tao; Li, Nianwu; Xu, Weihua; Li, Congju
Abstract: The pulsed output current of triboelectric nanogenerators (TENGs) has been used to charge the secondary battery recently. For a robust TENG with constant impetus, the output current will keep steady unless the external load resistance is changed. Therefore, the difference of charging current reflects the different charging resistance of the battery. Herein, the lithium–sulfur (Li–S) battery is charged by robust stable scale‐like structured TENG (SL‐TENG), and the real‐time charging current is recorded. The charging current increases with the initial potential rise, reflecting the oxidation process of the precipitated Li2 S and Li2 S2 with poor conductivity. Then the charging current keeps almost no change in flat charge plateau, accompanying with the main production of S8 2−, S7 2−, S6 2−, and S5 2− . Finally it shows a steep drop when the potential exceeds 2.4 V, accompanying with the second oxidation stage of the main production of S8 . Moreover, under SL‐TENG charging protocol, the capacity of Li–S battery increases obviously, and Li ions tend to deposit as large grain with smooth surface. SL‐TENG charging protocol is beneficial to improve the performance of Li–S battery, as well as helping to understand the charging mechanism to some extent. Abstract : The lithium–sulfur (Li–S) battery was charged by a robust stable scale‐like structured triboelectric nanogenerator (SL‐TENG). The different charging current at different depths of charge reflects the oxidation mechanism of Li–S battery. Moreover, the pulsed current protocol operated by SL‐TENG is beneficial to improving the performance of Li–S battery.